I’JAZUL QUR’AN TENTANG PENCIPTAAN LANGIT DAN BUMI: TELAAH TAFSIR SURAH AL-ANBIYA AYAT 30 DAN TEORI BIG BANG - Sultan, Zulfadli; Abubakar, Achmad; Ghany, Abdul (ELFALAKY: Jurnal Ilmu Falak, 2025)
This paper examines the miracle (i’jaz) of the Qur'an in the context of the creation of the heavens and the earth, focusing on the interpretation of Surah Al-Anbiya Verse 30 and its relevance to the Big Bang theory. This study aims to show the harmony between the teachings of the Qur'an and modern scientific discoveries. The method used is a qualitative method with a text analysis approach and literature review, the interpretations used as references include the Tafsir Al-Azhar by Buya Hamka. The results of this study reveal that the Big Bang Theory is in line with the explanation contained in QS. al-Anbiya' [21]: 30. In this verse, it is explained that the process of the creation of the earth began with the heavens and the earth uniting, then Allah separated the two. Meanwhile, in the Big Bang theory, the creation of the universe began with an explosion that produced matter, energy, planets, and various other elements. Although there are differences in the method of delivery, both the Qur'an and the Big Bang theory provide a deep understanding of the origins of the universe.